Surgical and oncological results after rectal resections with or without previous treatment for prostate cancer - Tomminen, T.; Huhtala, H.; Kotaluoto, S.; Veitonmäki, T.; Wirta, E.-V.; Hyöty, M. (Frontiers in Surgery, 2024)
Introduction Previous treatment for prostate cancer (PC) may potentially affect the surgical and oncological outcomes of subsequent rectal cancer surgery, but there are only a few studies regarding this particular group. In this study, we present the 3-year surgical and oncological results of rectal cancer patients who had received previous treatment for PC at a single Finnish tertiary referral centre. Material and methods Data regarding all male patients diagnosed with rectal cancer and treated at Tampere University Hospital (TAUH) between 1997 and 2016 were gathered from medical records. In total, this study included 553 rectal cancer patients who underwent curative surgery, and 54 of them (9.8%) had a prior history of treatment for prostate cancer. Results Patients in the PC group were older and had more comorbidities compared with those in the non-PC group. The PC patients had a significantly higher risk of permanent stoma compared with the non-PC patients (61.5% vs. 45.2%, respectively, p = 0.025). The PC patients seemed to have lower tumours than the non-PC patients (87% vs. 75%, respectively, p = 0.05). Overall, the 3-year overall survival (OS) for the PC and non-PC patients was 74.1% and 80.6%, respectively. No significant differences were observed between the study groups even in the age-adjusted comparison [hazard ratio (HR): 1.07, confidence interval (CI) 95%: 0.60–1.89]. In the univariable analysis, radically operated patients without a history of PC exhibited an improved overall survival, (HR: 2.46, 95% CI: 1.34–4.53, p = 0.004). However, only a higher age-adjusted Charlson comorbidity index (CCI) and a low tumour location (<10 cm) were found to have an independent prognostic impact on worse OS in the multivariable analysis (HR: 1.57, 95% CI: 1.36–1.82, p < 0.001 and HR: 2.74, 95% CI: 1.32–5.70, p = 0.007, respectively). No significant differences were observed between the groups in terms of disease-free or local recurrence-free survival. Conclusion Rectal cancer is more frequently found in the middle or lower part of the rectum in patients who have previously received treatment for prostate cancer. These patients also have a higher likelihood of requiring a permanent stoma. In radically operated rectal cancer, the PC group had a worse OS rate, according to the univariable analysis. However, the only independent prognostic factors for a worse OS that were highlighted in the multivariable analysis included a higher CCI and a low tumour location.